Additive hypocholesterolemic effect of psyllium and cholestyramine in the hamster: influence on fecal sterol and bile acid profiles - B P Daggy (Journal of Lipid Research, 1997)
Recent findings suggest that the effects of cholestyramine and psyllium in combination could be additive for cholesterol-lowering. We therefore examined the effect of both agents, alone and in combination, on lipoprotein cholesterol and neutral and acidic steroid excretion in the hamster. Animals (n = 8/group) were fed for 21 days, either a basal chow diet supplemented with 10% palm oil and 0.2% cholesterol, or one of four treatments consisting of the basal diet plus: 5.5% cellulose; 5% psyllium with 0.5% cellulose; 0.5% cholestyramine with 5% cellulose; or 5% psyllium with 0.5% cholestyramine. Psyllium and cholestyramine both had significant hypocholesterolemic effects, but in combination produced additive reductions in lipoprotein and hepatic cholesterol. Psyllium, cholestyramine, and the combination increased total bile acid excretion by 26%, 57%, and 79%, respectively. Psyllium affected only unconjugated bile acid excretion while cholestyramine also increased the excretion of conjugated and primary bile acids. Neither agent, nor the combination, affected fecal neutral sterol excretion. We conclude that, while both agents lower cholesterol by a mechanism of increased bile acid excretion, these studies indicate that psyllium does not bind bile acids in vivo and lend further support for the concomitant use of these agents for cholesterol-lowering.